Aggregation and removal of copper oxide (CuO) nanoparticles in wastewater environment and their effects on the microbial activities of wastewater biofilms. (September 2016) - Miao, Lingzhan; Wang, Chao; Hou, Jun; Wang, Peifang; Ao, Yanhui; Li, Yi; Geng, Nan; Yao, Yu; Lv, Bowen; Yang, Yangyang; You, Guoxiang; Xu, Yi
Graphical abstract: Highlights: Aggregation and adsorptive removal of CuO NPs in wastewater system were studied. Possible impacts of CuO NPs on biofilm were determined by assessing O2 penetration. 50 mg/L CuO NPs inhibited the microbial activities only in biofilm outmost layer. Protective mechanisms of the EPS matrix were discussed. Abstract: The transport behaviors of copper oxide (CuO) NPs in wastewater matrix and their possible impacts on microbial activities of stable wastewater biofilms cultivated in a lab scale rotating biological contactor (RBC) were investigated. Significant aggregation of CuO NPs was observed in the wastewater samples, depending on their mass concentrations. Extracellular polymeric substance (EPS)-adsorbed copper accounted for a large proportion of the total copper accumulated in biofilms. The microelectrode profiles showed that a single pulse exposure to 50 mg/L CuO resulted in a deeper penetration depth of oxygen in biofilms compared to the CuO NP free biofilms. The maximum oxygen consumption rate shifted to the deeper parts of biofilms, indicating that the respiration activities of bacteria in the top region of the biofilms was significantly inhibited by CuO NPs. Biofilms secreted more EPS in response to the nano-CuO stress, with higher production of proteins compared to polysaccharides.